Teaching Culture in the Foreign Language Classroom: A Reflective Model - Zamora Salazar, Eduardo (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2013)
This paper analyzes how ten in-service teachers currently studying in the Master?s Program in Second Languages and Cultures at Universidad Nacional have undergone a four-month process which focused on their growth in multicultural competencies for cross-cultural communication, cultural awareness and understanding, and the development of techniques and activities to promote the learning of such values in their classes. The participants designed lesson plans that addressed cultural topics, provided and received peer feedback, conducted peer-teaching observations, put together a didactic unit for teaching culture, created a blog about their experiences, and reflected about ways to teach culture in their classes.